Quasi-synchronization of neural networks with parameter mismatches and delayed impulsive controller on time scales. (August 2019) - Huang, Zhenkun; Cao, Jinde; Li, Jiamin; Bin, Honghua
Abstract: This paper is concerned with quasi-synchronization issue of neural networks which take parameter mismatches and a delayed impulsive controller into account on time scales. Due to the existence of hybrid time domains, there exists novel inherent quasi-synchronization mechanism which will show relationships between mismatching parameters and delayed impulses. Based on calculus of time scales and the direct Lyapunov method, some scale-type criteria to achieve the quasi-synchronization of neural networks under impulsive control are derived. Finally, a numerical simulation is presented to illustrate the effectiveness of theoretical analysis.